2005
DOI: 10.1007/11555261_68
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Missing Data: Graph Interpretation User Study

Abstract: Abstract. Most visualization tools fail to provide support for missing data. In this paper, we identify sources of missing data and describe three levels of impact missing data can have on the visualization: perceivable, invisible or propagating. We then report on a user study with 30 participants that compared three design variants. A between-subject graph interpretation study provides strong evidence for the need of indicating the presence of missing information, and some direction for addressing the problem. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…The third alternative is perhaps the most common approach, although there are known problems in it even in a 1D situation (Eaton et al, 2005). In this case, we could use the value zero as a reasonable marker for missing information on mileage or horsepower, since the users would probably interpret them correctly.…”
Section: Missing Data In Parallel Coordinate Visualizationsmentioning
confidence: 99%
“…The third alternative is perhaps the most common approach, although there are known problems in it even in a 1D situation (Eaton et al, 2005). In this case, we could use the value zero as a reasonable marker for missing information on mileage or horsepower, since the users would probably interpret them correctly.…”
Section: Missing Data In Parallel Coordinate Visualizationsmentioning
confidence: 99%
“…In order to draw meaningful and accurate conclusions from the data, visualization tools should represent missingness and uncertainty clearly. For instance, a recent study demonstrated that participants interpreting graphics with missing data tended to misinterpret results, but with equal confidence in their interpretations as those viewing more complete graphics [148]. Similarly, geographic analyses are known to be sensitive to overestimation of rates in small populations, which often correspond to large, sparsely populated regions, resulting in visual biases in interpreting choropleth maps [130].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of methods for dealing with missing data in information visualisation applications [18]. These include the use of dedicated visual attributes, annotation and animation.…”
Section: Visualisaing Missing Datamentioning
confidence: 99%